Peran Media Massa dalam Mencegah Konflik - Bend Abidin Santosa (Jurnal Aspikom)
Indonesia is a country with diversified ethnics, religions and races. Without spirit of tolerance this condition can emerge conflict and disunion. Mass media is one of instruments in mass communication process that filter and select news and conflict to be presented. This study investigates how mass media presents conflict with peace journalism principle as an alternative solution in handling conflicts in Indonesia. This research uses descriptive qualitative method and framing analysis. Result shows that mass media have significant roles in constructing public opinion since they have power to construct reality in public in disseminating information and values to community for achieving tolerance.